CA6 impact on the corrosion behavior of cement-bonded spinel-containing refractory castables: an analysis based on thermodynamic simulation - Tomba Martinez, Analia Gladys (2014)
This work focuses on the evaluation of the corrosion behavior of Al2O3-MgO cement-bonded castables based on thermodynamic calculations, in order to understand the reaction steps and some scientific and technological issues that still need to be better explained when such materials come into contact with basic industrial slags at high temperatures. Special attention was given to analyzing the role played by the calcium hexaluminate phase (CA6) during the first heating stage of the samples and their further chemical attack. Experimental measurements (cup tests at 1500 °C) and thermodynamic simulations were carried out considering a basic slag (CaO/SiO2=4.2) and four refractory castables with different spinel (MgAl2O4) sources (pre-formed or in situ) and with or without silica fume (0 or 1 wt%). Considering the attained results, a novel corrosion mechanism is proposed pointing out that a suitable design of the castable compositions can induce the formation of CA6 at the border of the coarse aggregates, preventing their further dissolution and increasing the overall wear resistance of these refractories. In Addition, incorporating optimized contents of silica fume and cement to the spinel-containing castables helps to master the generation of the CA6 and CA2 protective layers, resulting in a lower chemical attack at high temperatures.